The London in Pride and Prejudice and Zombies (2009) and its 2016 Filmic Adaption - Choedphong Uttama (Thoughts, 2021)
This paper aims to read the zombies in Pride and Prejudice and Zombies (2009) and its 2016 filmic adaption by Burr Steers as embodiments of the lower classes and foreign invaders in Austen’s novels. Zombies, as popular monsters, are linked with social disorder, filth and disease, all of which the upper social strata in Jane Austen’s time believed to be associated with the lower classes. By the addition of a zombie outbreak to Austen’s Pride and Prejudice, Grahame-Smith manifests Austen’s or the late-eighteenth-century gentry’s and the upper classes’ anxiety about the lower social classes and the masses in London with their tendency to stage riots and spread disease. In the filmic adaption, the zombies embody foreign invaders attempting to destroy London which stands for the nation. The collapse of London suggests that the film follows the popular cinematic representation of the city in apocalyptic zombie films. To achieve its aim, this paper employs a socio-historical approach by analyzing Austen’s works against the socio-historical context of the late eighteenth and early nineteenth centuries with regard to the lower social orders and foreign invasion, revealing the threats they pose and illustrating how these threats are captured by zombies.
Keywords: Crime and Detective Fiction Studies; Gothic Literature and Media Analysis